Digital Marketing Training Assistance for Batik Business Actors in Klampar Village Community - Ni'mah, Rika Miftahun; Rakhmawati, Intan Lisa; Hapsari, Mutiarizki; Nusantara, Bagus Aji; Syaiful, Dimas Surya Purnomo (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2023)
This community service activity aims to educate and train the batik artisan community in Klampar village about digital marketing. This will help them to reach a broader market and compete effectively with products that have entered the digital marketing sphere. This community service method uses the Asset Based Community Development (ABCD) approach, based on assets, strengths, and potentials in Klampar village. Highlighting Pamekasan's batik assets will contribute to global recognition, preserving the cultural heritage of Klampar residents. After the training, the activity was evaluated with an interactive discussion regarding the batik sales stats. This community service activity has enhanced their understanding of digital marketing for promoting products in the digital era. This includes increased sales of products marketed through digital channels and a heightened awareness of the importance of global distribution in selling a product globally by using the features in the Shopee and WhatsApp Business applications as a medium for digitalising batik marketing.